2006
DOI: 10.1681/asn.2005080796
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Reconstruction of the Mouse Nephron

Abstract: Renal function is crucially dependent on renal microstructure which provides the basis for the regulatory mechanisms that control the transport of water and solutes between filtrate and plasma and the urinary concentration. This study provides new, detailed information on mouse renal architecture, including the spatial course of the tubules, lengths of different segments of nephrons, histotopography of tubules and vascular bundles, and epithelial ultrastructure at well-defined positions along Henle's loop and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
117
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 38 publications
(32 reference statements)
9
117
2
Order By: Relevance
“…We used the rat kidney in our work because of the enormous amount of physiologic data, including data on the concentrating mechanism, available for this species. However, our preliminary work and studies by others (44,45) suggest that the three-dimensional relationships in the mouse renal medulla are similar to those in the rat. Our preliminary studies also indicate that rodent and human inner medullary architecture share fundamental similarities.…”
Section: Introductionsupporting
confidence: 60%
“…We used the rat kidney in our work because of the enormous amount of physiologic data, including data on the concentrating mechanism, available for this species. However, our preliminary work and studies by others (44,45) suggest that the three-dimensional relationships in the mouse renal medulla are similar to those in the rat. Our preliminary studies also indicate that rodent and human inner medullary architecture share fundamental similarities.…”
Section: Introductionsupporting
confidence: 60%
“…2G), and anti-CLCK1 (Fig. 2K) antibodies (41,43,50,55,58,78,79). These staining patterns indicate that CBS (and CTH) is predominantly expressed in the proximal convoluted tubules (PCT) and proximal straight tubules (PST).…”
Section: Coexpression Of Cbs and Cth In Renal Proximal Tubulesmentioning
confidence: 88%
“…Recycling first was demonstrated by Lassiter et al (55), who showed that the mass flow rate of urea in the superficial tubule exceeds the filtered load of urea. It has been proposed (54) that a major element of urea secretion into Henle's loop is via transfer from the vasa recta to the thin descending limbs of short-loop nephrons in the vascular bundles of the outer medulla, where these two structures are in close apposition (56,57). The chief urea transporter of the vasa recta is UT-B, whereas the chief urea transporter in the thin descending limbs is UT-A2 ( Figures 1 and 3).…”
Section: Urea Recyclingmentioning
confidence: 99%